Military justice during the war : a letter from the Judge Advocate General of the Army to the Secretary of War in reply to a request for information (Government Printing Office, 1919)
This document is comprised of two letters. The first is from Secretary of War Newton D. Baker, dated March 1, 1919 and addressed to Major General Enoch H. Crowder, Judge Advocate General. In his letter, Secretary Baker expresses concern over recent harsh criticisms of the U.S. system of military justice and requests that General Crowder answer these criticisms by providing "a concise survey of the entire field" so as to restore the confidence of all those concerned. General Crowder's reply, dated March 10, 1919, follows. After introductory remarks on "prior efforts to revise the Articles of War" and the extent of his own "personal responsibility for the administration of military justice" during the previous two years, General Crowder presents detailed information on three individual cases, addresses at length the general defects that allegedly exist in military justice, and concludes with recommendations.